2019
DOI: 10.1177/0361198119827574
|View full text |Cite
|
Sign up to set email alerts
|

Tracking the Impact of a Toll Increase on Managed Lane Travel Behavior

Abstract: Tolled managed lanes (ML) are an innovative way to increase capacity and regulate demand on roadways. They are still relatively new and a lot remains unknown about how travelers choose to use MLs or not. This paper uses disaggregate real-world travel data of travelers who choose between paying a toll to use ML or travel toll free on the adjacent general purpose lanes (GPL). The travel behavior before and after a toll increase is evaluated. The change in toll rates did not affect the overall ML use as anticipat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Note that this change assumes all travelers make economically rational decisions based on their VTT. It has been shown that most travelers do not (27,47) and that many travelers feel they save more travel time on MLs than is the case (45). Therefore, the assumption of economically rational decision making is likely inaccurate and revenue loss is probably not as high as 17.4%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Note that this change assumes all travelers make economically rational decisions based on their VTT. It has been shown that most travelers do not (27,47) and that many travelers feel they save more travel time on MLs than is the case (45). Therefore, the assumption of economically rational decision making is likely inaccurate and revenue loss is probably not as high as 17.4%.…”
Section: Resultsmentioning
confidence: 99%
“…The ML system studied in this paper is Katy Freeway between SH 6 and west I-610 in Houston, Texas. Many researchers (2,10,(26)(27)(28) have conducted surveys and studies on drivers in the area and constructed VTT distributions based on income groups and trip situations (i.e., urgency of the trip). The following fixed percentages of income groups are assumed based on a mix of traveler survey and census data from Houston (10).…”
Section: Value Of Travel Time Distributionsmentioning
confidence: 99%
“…Both field (Burris & Ashraf, 2019;Burris & Brady, 2018) and experimental analysis (Selten et al, 2004(Selten et al, , 2007 of coordination behavior in traffic studies reveal patterns of behavior that are not consistent with agents responding to changes in parameters in ways that will lead to systems equilibrating. Both suggest that informational interventions may increase payoffs for drivers and system equilibration.…”
Section: Discussionmentioning
confidence: 99%
“…Among the remaining 15% of travelers who made an active decision of choosing between the lanes, many made counterintuitive choices based on their travel time savings and toll rate ( 1 ). The observed commuter choice does not fit standardized rational-choice models in the above context and new methods are required to address this fundamental problem—the assumption that all travelers are choosing between MLs and GPLs ( 1 , 2 ).…”
mentioning
confidence: 99%